Cover, Content, and Editorial Note from Borneo J Med Lab Tech Vol. 2 No. 1 October 2019 - Chief Editor of Borneo J Med Lab Tech (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Alhamdulillahirabbil ‘alamin. After a long wait for almost 12 years from the first stand, finally the scientific journal of the Department of Analyst Health (Medical Laboratory Technology) Universitas Muhammadiyah Palangkaraya can be published. BJMLT published every 6 months (2 issues/year) every October and April. The aim of this journal is to publish high-quality articles dedicated to all aspects of the latest outstanding developments in the field but not limited to Blood transfusion, Clinical Chemistry, Hematology, Histopathology, Immunology, Microbiology, Parasitology, Toxicology, Food and Beverage Analysis, Molecular Biology, Medical Biology, and related fields that are of interest to medical laboratory technologies, such as epidemiology, health promotion, professional ethics, and laboratory management